On certain properties of three parametric kinds of Apostol-type unified Bernoulli-Euler polynomials - William Ramírez; Can Kızılateş; Daniel Bedoya; Clemente Cesarano; Cheon Seoung Ryoo (AIMS Mathematics, 2025)
In this paper, we define the three parametric types of Apostol-type unified Bernoulli-Euler polynomials. We present fundamental properties of these polynomials through the utilization of their generating functions. Furthermore, we derive the partial derivatives of these polynomials. Subsequently, we introduce bivariate polynomials and determine their zeros, graphical representations, and approximation values for specific parameters.